2011
DOI: 10.1111/j.1475-6765.2011.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal vote‐seeking in flexible list systems: How electoral incentives shape Belgian MPs' bill initiation behaviour

Abstract: It is well known that different types of electoral systems create different incentives to cultivate a personal vote and that there may be variation in intra‐party competition within an electoral system. This article demonstrates that flexible list systems – where voters can choose to cast a vote for the list as ordered by the party or express preference votes for candidates – create another type of variation in personal vote‐seeking incentives within the system. This variation arises because the flexibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 40 publications
3
64
0
5
Order By: Relevance
“…From a practical perspective, the main difference is that private member bills have a small chance of becoming law, while EDMs are purely signaling devices. Recent research suggests that sponsoring legislation is a response to vote-seeking incentives in a wide range of legislative systems (Bowler 2010;Bra¨uninger, Brunner and Da¨ubler 2011;Brunner 2012). Most notably, Loewen et al (2013) demonstrate that private member bills have a positive causal effect on electoral outcomes in Canada by taking advantage of the randomization used to select bills for consideration.…”
Section: Edms In Contextmentioning
confidence: 99%
“…From a practical perspective, the main difference is that private member bills have a small chance of becoming law, while EDMs are purely signaling devices. Recent research suggests that sponsoring legislation is a response to vote-seeking incentives in a wide range of legislative systems (Bowler 2010;Bra¨uninger, Brunner and Da¨ubler 2011;Brunner 2012). Most notably, Loewen et al (2013) demonstrate that private member bills have a positive causal effect on electoral outcomes in Canada by taking advantage of the randomization used to select bills for consideration.…”
Section: Edms In Contextmentioning
confidence: 99%
“…Mixed systems offer opportunities to cultivate a personal vote when constituencies are able to amend the list or vote for single candidates. As Bräuninger et al (2012a) have recently shown, incentives to cultivate a personal vote can even vary within flexible list systems, if there is district-level variation in the constituencies' use of preference votes and in the rules of intra-party seat allocation.…”
mentioning
confidence: 99%
“…However, district magnitude as an indicator of constituency crowdedness has been disputed (Crisp et al ), leaving the presence or absence of an intra‐party competitor for re‐nomination as the main difference between electoral districts. In this vein, Bräuninger et al () find that incentives for personal vote‐seeking behaviour varies across electoral districts along with the propensity of voters to make use of preferential voting systems. Crisp et al () extend this logic to combinations of electoral incentives and party nomination rules, finding that MPs who face personalizing effects will be more active in initiating geographically targetable bills.…”
Section: Mp Behaviour and Individual Issue Emphasesmentioning
confidence: 99%
“…The importance of individual MP behaviour is reflected by the rising interest of the parliamentary behaviour literature in the individualization of political behaviour. Most of these studies have focused on the individualization of campaigns (Zittel & Gschwend ; Eder et al ; Hennl ) or open‐access parliamentary instruments (Bowler ; Martin ; Bräuninger et al ). Only recently has the literature begun to look at legislative speech from an individual MP perspective asking which parliamentarians are allocated access to the parliamentary floor (Proksch & Slapin ; Bäck et al ; Bäck & Debus ).…”
Section: Introductionmentioning
confidence: 99%